Essential study skills : the complete guide to success at university - Burns, Tom.; Sinfield, Sandra (London ; Thousand Oaks, Calif. : SAGE Publications, 2003)
A complete practical guide to academic success covering everything from what it means to be a university student to how to succeed in exams.
Includes bibliographical references and index.
Keywords: Study skills -- Handbooks, manuals, etc; College student orientation -- Handbooks, manuals, etc